1997
DOI: 10.1038/sj.onc.1200864
|View full text |Cite
|
Sign up to set email alerts
|

The Evi-1 proto-oncogene encodes a transcriptional repressor activity associated with transformation

Abstract: The myeloid transforming gene Evi-1 encodes a protein with two zinc ®nger domains, designated ZF1 and ZF2, with distinct DNA binding speci®cities. For the ®rst time we demonstrate that Evi-1 has transcriptional repressor activity which is directly proportional to the amount of Evi-1 protein in cells. Repression has been observed with two distinct promoters: the minimal HSV-1 tk promoter and a VP16 inducible adenovirus E1b minimal promoter. Optimal repression is DNA binding dependent and is mediated by either Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 22 publications
0
95
0
1
Order By: Relevance
“…32 In contrast, studies using CAT reporters that contained either the first or second EVI1 target sites upstream of the HSVtk promoter found that EVI1 dramatically expressed the activity of these reporters. 28,33 More recently, studies by Bartholomew et al 34 showed that EVI1 represses synthetic promoters in which the zinc fingers consensus site was cloned upstream of the herpes simplex virus (HSV) thymidine kinase (tk) promoter or of the adenovirus minimal promoter, confirming the role of EVI1 as transcriptional repressor. In addition, these investigators showed that the repression function is localized in a stretch of proline-rich residues located between the two groups of zinc fingers (Figure 1a), and it can be completely abolished by an internal deletion spanning the proline-rich stretch.…”
Section: Evi1 Expression and Functionmentioning
confidence: 94%
See 2 more Smart Citations
“…32 In contrast, studies using CAT reporters that contained either the first or second EVI1 target sites upstream of the HSVtk promoter found that EVI1 dramatically expressed the activity of these reporters. 28,33 More recently, studies by Bartholomew et al 34 showed that EVI1 represses synthetic promoters in which the zinc fingers consensus site was cloned upstream of the herpes simplex virus (HSV) thymidine kinase (tk) promoter or of the adenovirus minimal promoter, confirming the role of EVI1 as transcriptional repressor. In addition, these investigators showed that the repression function is localized in a stretch of proline-rich residues located between the two groups of zinc fingers (Figure 1a), and it can be completely abolished by an internal deletion spanning the proline-rich stretch.…”
Section: Evi1 Expression and Functionmentioning
confidence: 94%
“…In addition, these investigators showed that the repression function is localized in a stretch of proline-rich residues located between the two groups of zinc fingers (Figure 1a), and it can be completely abolished by an internal deletion spanning the proline-rich stretch. 34 …”
Section: Evi1 Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26]55,56 The KRAB-domain represses the activity of CMV-promoter through direct communications with TATA box-dependent basal transcription machinery, 18,55 whereas mSIN3B interacts with essential DNAbinding proteins that place it in a promoter context in which it can repress transcription by recruiting proteins that condense chromatin by histone deacetylation. 19 In contrast to KRAB-A or mSIN3B, the Zik1-repressor domain does not repress gene transcription from the CMV gal -promoter and some of the other repressor domains showed only weak repression of CMV galactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors for repressor fusion proteins of GAL4-DBD were kindly provided by: L Lania, Neaples, Italy (KRAB-A), 18 RA DePinho Boston, USA (m-SIN3B-SF and m-SIN3B-LF), 19 DJ Hall, Philadelphia, PA, USA (ZF87/MAZ), 20 K Bomsztyk, Seattle, USA (ZIK1), 21 LM Staudt, Bethesda, MD, USA (BCL-6), 22 C Bartholomew, Glasgow, Scotland (EVI-1), 23 Y Shi, Boston, USA (YY), 24 H-S Ro, Halifax Canada (AEBP2) 25 and A Bird, Edinburgh, UK (MeCP2 170-310 and MeCP2 209-492). 26 …”
Section: Cell Lines and Plasmidsmentioning
confidence: 99%